Caries Management with the International Caries Detection and Assessment System: Early Pit and Fissure Lesions - Jan Mitchell; Martha Brackett; Mario Romero (Association of American Medical Colleges, 2016)
Abstract Introduction As traditional techniques for detecting occlusal caries by probing fissures with sharp explorers have been discredited, alternate techniques for diagnosing caries in this location have been proposed, such as the International Caries Detection and Assessment System (ICDAS). However, given the novelty of the ICDAS, it became apparent that modules needed to both teach concepts and skills and standardize the faculty teaching of these concepts. Methods This 4-hour flipped classroom session starts with a short quiz followed by a brief review of key concepts from the presession tutorial. Next, students split into small groups and use a worksheet based on ICDAS criteria to diagnose and create a treatment plan for selected teeth. Finally, the learners perform sealant and preventive resin restoration procedures as appropriate on their selected teeth. All teaching materials are provided to faculty, who are encouraged to become familiar with them in advance. Results The student response has been very positive; a common student comment has been "I don't know how I would have had the nerve to treat a patient without this practice." A retrospective look at patient charts shows a dramatic reduction in the number of treatment plan items changed by faculty following the activity. Discussion Based on feedback, the exercise was moved from the third year to the second year so students could have more chances to practice prior to seeing patients in the second half of the second year. Further, the exercise has been expanded from two to four sessions, with this being the first.